Diagnostic Accuracy of Risk of Malignancy Index RMI in Patients with Adnexal Mass - Neelum Zahir, Saima Ali, Rukhsana (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Gynecological cancers often begin in the ovaries. Malignant pelvic masses may often be predicted using the Risk of Malignancy Index (RMI). Objective: To evaluate the RMI for its ability to differentiate between benign and malignant adnexal masses. Methods: A cross-sectional study in a gynecology and obstetrics OPD of Saidu Group Of teaching hospital,swat was carried out. 55 women who were hypothesized to have adnexal masses were included after informed consent. Each patient menopausal status, ultrasonography (USG) score and blood CA-125 level was measured. For every participant, the RMI was determined. Results: Thirty-five of the recruited women had noncancerous adnexal mass, whereas twenty had cancerous ones. Benign adnexal mass was seen in 19 premenopausal women and 16 postmenopausal women, and in malignant adnexal mass there were 13 premenopausal women and 7 postmenopausal women. Participants’ mean ages were 44 years for benign adnexal mass and 40 years for malignant adnexal mass. USG score and CA-125 have significant variation between the benign and malignant adnexal masses, with p value of 0.000. High sensitivity (80%) and specificity (71.3%), as well as positive (77.3%) and negative (74.7%) predictive values, were found for the RMI at a cut-off of <200 when used to differentiate between benign and malignant adnexal masses. Conclusion: In conclusion, the RMI seems to be a trustworthy, easy, and cost-effective technique for clinical distinction between benign and malignant adnexal masses. Keywords: adnexal mass, USG score, ovarian cancer, ovary malignancies